The Ploskie Sopki volcanic massif: Geology, petrochemistry, mineralogy, and petrogenesis (Klyuchevskoi Volcanic Cluster, Kamchatka) - Flerov G.B.; Churikova T.G.; Anan'ev V.V. (My University, 2017)
This paper is concerned with the geological history and petrology of a major polygenic volcanic edifice dating back to Upper Pleistocene to Holocene time. This long-lived volcanic center is remarkable in that it combines basaltic and trachybasaltic magmas which are found in basaltic andesite and trachybasaltic– trachyandesite series. The inference is that the coexisting parent magmas are genetically independent and are generated at different sources at depth in an upper mantle volume. The associated volcanic rocks have diverse compositions, stemming from a multi-stage spatio–temporal crystallization differentiation of the magmas and mixing of these in intermediate chas.
Keywords: 38.33.17 Геохимия природных процессов; Крестовский; Плоский; Ушковский